Antimutagenic and genoprotective effects of Saraca asoca bark extract. (August 2015) - Nag, Debarati; Ghosh, Manosij; Mukherjee, Anita
Aim of the study: Traditionally herbal formulations have been used effectively for the management of disorders that are now being accepted worldwide. Saraca asoca bark extract (SAE) finds use in traditional herbal medicine. In the present study, SAE were studied for their antioxidant, antimutagenic, and antigenotoxic properties. Methods: SAE were evaluated for antimutagenic property in Salmonella strains (TA97a, TA98, TA100, and TA102), in the presence and absence of metabolic activation (S9). The SAE was also studied for antigenotoxic property against cyclophosphamide (CP) in Swiss albino male mice in vivo . The extract was analyzed using high-performance liquid chromatography (HPLC). Results: The study reveals antimutagenic property of the bark extract in Salmonella strains in the presence and absence of metabolic activation (S9). The study reports antigenotoxic property of the bark extract against CP in vivo . Thiobarbituric acid reactive species assay on the bark extract revealed antioxidant property. HPLC revealed the presence of two peaks corresponding to gallic acid and (−)-epicatechin, respectively. Conclusion: The study clearly reveals the antimutagenic and antigenotoxic properties of SAE.